The Degree of Sustainable Leadership ‎Practicing by Basic Education Schools’ ‎Principals in Oman: An Empirical Study of ‎Al-Batinah South Governorate - Al-Mahdy ‎, Yasser; Lashin‎, Mohammed; Al-Balushi, Asya (Jordan Journal of Educational Sciences, 2023)
This study aimed to investigate the degree of sustainable leadership practiced by the schools’ principals of the second-round basic education in Al-Batinah South Governorate, Sultanate of Oman and identify the differences according to the variables of gender and experience. The study sample consisted of (383) male and female teachers. The descriptive approach has been used through a questionnaire consisting of four dimensions of sustainable leadership (human resources, strategic distribution, deep learning, environmental and social responsibility). The results showed that the degree of sustainable leadership practiced by the schools’ principals of the second-round basic education in Al-Batinah South Governorate was of a moderate degree from the teachers' point of view. The results also showed statistically significant differences for the sustainable leadership attributed to the gender variable in favor of females. There were no statistically significant differences for sustainable leadership attributed to the years of experience variable in all sub-aspects at the level of the total degrees